CHEMICAL COMPOSITION AND EVOLUTIONARY STATUSOF SPECTRAL BINARY STAR 12 PER - Leushin, V. V.; Kuznetsov, M. K. (Одеські астрономічні публікації, 2008)
The star 12 Per is known as a spectroscopic and interferometeric binary. The high resolution spectra in 3700 - 8000 Å band were obtained with the 2 m telescope at Peak Terskol. A detailed analysis of the atmosphere of system's components was carried out using the collected data.